Intrathecal Baclofen Associated With Improvement of Consciousness Disorders in Spasticity Patients. Issue 7 (18th December 2013) - Margetis, Konstantinos; Korfias, Stefanos I.; Gatzonis, Stylianos; Boutos, Nick; Stranjalis, George; Boviatsis, Efstathios; Sakas, Damianos E.
<x xml:space="preserve">Abstract</x> Objective Intrathecal baclofen (ITB) pump is a therapeutic option for persistent vegetative state and minimal conscious state patients that have associated spasticity. We investigated whether this treatment modality can affect their level of consciousness. Method In this prospective, open label, observational study, we implanted ITB pumps for the treatment of spasticity in eight patients with disorders of consciousness (vegetative state and minimally conscious state) and we followed them with the Coma Recovery Scale‐Revised, the Eastern Cooperative Oncology Group (ECOG) performance scale, and the Modified Ashworth spasticity scale. Baclofen dose and complications also were noted. Results The offending pathologies were traumatic brain injury in six, anoxia due to cardiac arrest in one, acute obstructive hydrocephalus in one. Two of the patients showed a marked, persistent improvement that fulfilled the criteria of emergence from minimally conscious state. Two of patients had their ITB pumps prematurely removed because of complications. The ECOG score was 4 for all patients and did not change during the study. Conclusion ITB might be associated with a significant improvement in the disorder of consciousness of two patients from a total of six that had a chronic ITB treatment.